Registered Report Evidence Suggests No Relationship Between Objectively Tracked Video Game Playtime and Wellbeing Over 3 Months - Ballou,N; Sewall,CJR; Ratcliffe,J; Zendle,D; Tokarchuk,L; Deterding,S (Technology, Mind, and Behavior, 2024)
Recent years have seen intense research, media, and policy debate on whether amount of time spent playing video games (“playtime”) affects players’ well-being. Existing research has used cross-sectional designs with easy-to-obtain but unreliable self- report measures of playtime or, in rare instances, obtained industry data on objectively tracked playtime but only for individual games, not a player’s total playtime across games. Further, researchers have raised concerns that publication bias and a lack of differentiation between exploratory and con rmatory research have undermined the credibility of the evidence base. As a result, we still do not know whether well-being affects playtime, playtime affects well-being, both, or neither. To track people’s playtime across multiple games, we developed a method to log playtime on the Xbox platform. In a 12-week, six-wave panel study of adult U.S./U.K. Xbox-predominant players (414 players, 2036 completed surveys), we investigated within-person temporal relations between objectively measured playtime and well-being. Across multiple preregistered model speci cations, we found that the within-person prospective relationships between playtime and well-being, or vice versa, were not practically signi cant—even the largest associations were unlikely to register a perceptible impact on a player’s well-being. These results support the growing body of evidence that playtime is not the primary factor in the relationship between gaming and mental health for the majority of players and that research focus should be on the context and quality of gameplay instead.